2022
DOI: 10.3390/polym14030388
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Mechanical, and Morphological Performances of Arrowroot (Maranta arundinacea) Fiber Reinforced Arrowroot Starch Biopolymer Composites

Abstract: This research is driven by stringent environmental legislation requiring the consumption and use of environmentally friendly materials. In this context, this paper is concerned with the development and characterization of thermoplastic arrowroot starch (TPAS) based biocomposite films by incorporating arrowroot fiber (AF) (0−10%) into a glycerol plasticized matrix by using the solution casting method. Developed TPAS/AF composite films were investigated, such as physical, morphological (FESEM), tensile, and tear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 71 publications
1
10
0
4
Order By: Relevance
“…Thus, a more porous, coarser, and thicker structure of the 2% DPE-incorporated film was observed compared to the control (0% DPE) biopolymer film. Similar findings were reported in studies on the contribution of fiber addition to an increase in the thickness of starch-based films [ 57 , 58 , 59 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, a more porous, coarser, and thicker structure of the 2% DPE-incorporated film was observed compared to the control (0% DPE) biopolymer film. Similar findings were reported in studies on the contribution of fiber addition to an increase in the thickness of starch-based films [ 57 , 58 , 59 ].…”
Section: Resultssupporting
confidence: 90%
“…The interactions through the non-covalent hydrogen bonding of the polysaccharide chain of rice starch-pectin biocomposite matrix with the polyphenols in the dragon fruit peel extract possibly led to the forming of the complex inclusion (V-type amylose) [ 54 , 55 , 56 ]. This helix structure of the polyphenols and polysaccharide chains of the starch-pectin biopolymer matrix limited the movement of the polysaccharide chain [ 57 ]. Thus, a more porous, coarser, and thicker structure of the 2% DPE-incorporated film was observed compared to the control (0% DPE) biopolymer film.…”
Section: Resultsmentioning
confidence: 99%
“…Fiber addition had a similar effect on the thicknesses and densities of biocomposite films, according to Edhirej et al [14] who studies cassava bagasse reinforced thermoplastic cassava starch, sugar palm starch biocomposite films [32], seaweed/sugar palm fiber reinforced ther-moplastic sugar palm starch/agar hybrid composites [33], thermoplastic films based on Dioscorea hispida starch [34] and arrowroot fiber reinforced arrowroot starch biopolymer composites [35]. Nonetheless, the lower densities of composite samples made them desirable materials, particularly for applications that demand compactness and ease of use.…”
Section: Physical Properties Of Hybrid Filmsmentioning
confidence: 95%
“…Composites made of natural fibers are less resistant to moisture because hydroxyl and polar groups are moisture-absorbers [18,25,35,40,41]. Therefore, the influence of the water absorption rate on the CS-K/CH hybrid composites properties was investigated.…”
Section: Water Absorption Studymentioning
confidence: 99%
“…It has been reported that the different synergistic effects of starch and hydrocolloids could be related to the physicochemical differences of hydrocolloids such as solubility [ 21 , 22 , 23 ], intrinsic viscosity [ 24 ], extended conformation [ 25 , 26 ], antioxidant potential [ 27 , 28 ], hydrogen bonding capacity [ 29 ], flexibility [ 30 ], and temperature of gel formation [ 24 , 31 , 32 ]. The diversity of hydrocolloid molecular structures, especially for the differences in the side chain, usually contributes to the variations in physicochemical properties [ 33 ].…”
Section: Introductionmentioning
confidence: 99%